Landscape, agrobiodiversity, and local knowledge in the protected area “Quebrada de los Cuervos y Sierras del Yerbal,” Uruguay - Puppo, María; Gianotti, Camila; Calvete, Alejandra; Leal, Alejandra; Rivas, Mercedes (Frontiers in Sustainable Food Systems, 2023)
Agrobiodiversity and local knowledge are fundamental components in the domestication and structuring of rural landscapes. In a context of threats to agroecosystems resulting from changes in production systems and rural-urban migration processes, the conservation and valorization of agrobiodiversity is a pressing challenge. "Quebrada de los Cuervos and Sierras del Yerbal" is a protected landscape in Uruguay where a rural community of approximately 30 families with a longstanding tradition resides. The research aimed at identifying current and abandoned (taperas) domestic contexts, and the plant genetic resources found in the area, categorizing their uses and management practices through interviews and participant observation. Ethnographic research revealed 185 species (121 exotic, 64 native) with diverse growth habits, ten categories of uses, and eleven categories for management practices. The differences found between houses and taperas revealed that the abandonment of activities in rural areas is a relevant factor in the loss of agrobiodiversity. Among the 185 species, a notable group of plant genetic resources of high cultural significance is recognized due to their consensus of use, frequency of management practices, and number of uses. These include introduced fruit trees (peach, citrus, and fig) and native fruit trees (guayabo del país, pitanga, and arazá), vegetable landraces, native trees with multiple uses, yerba mate, and medicinal species such as Aristolochia fimbriata. For domestic contexts, a model of spatial distribution of agrobiodiversity is proposed, cultivated spaces where the plant genetic resources are located in home gardens and small plots, managed spaces where the resources are found in the surroundings of houses, and promoted and intervened wild spaces where the species are used from natural grasslands and wild environments. The obtained information reaffirms the need to conserve this biocultural landscape, placing agrobiodiversity and local knowledge as a focal point in the protected area. The management plan must be formulated with active participation from the rural community, aiming for valorization through integration into agroecological production chains, among other possibilities.